CARBON EMISSION DISCLOSURE: VIEWED FROM THE PERSPECTIVES OF ACCOUNTING, MARKET, AND ENVIRONMENTAL PERFORMANCE IN HIGHLY POLLUTING COMPANIES IN INDONESIA - Fuadi, Fauzan; Sinatria, Naufal; Fadhilah, Husein (Jurnal Aplikasi Akuntansi, 2025)
This study examines the determinants of carbon emission disclosure (CED) among high-polluting industries in Indonesia by integrating accounting performance (ROA), market performance (Tobin’s Q), and environmental performance (PROPER) into a multidimensional analytical model. The research utilises 114 firm-year observations from 30 listed companies on the Indonesia Stock Exchange (IDX) between 2021 and 2024, selected through purposive sampling. Multiple linear regression analysis was conducted using STATA. The regression model explains 35.6% (R² = 0.356) of the variation in carbon emission disclosure, indicating a moderate explanatory power of the independent variables. The results reveal that Tobin’s Q and PROPER positively affect carbon emission disclosure, indicating that market perception and environmental rating systems encourage greater transparency. Conversely, ROA shows no significant relationship with disclosure practices, suggesting that profitability alone does not influence firms’ environmental reporting behaviour. This study focuses on Indonesia, one of the world’s largest carbon emitters, where high-polluting industries such as mining, energy, and chemicals play a dominant role but often exhibit inconsistent or superficial disclosure practices. This study highlights that market expectations and environmental performance are more decisive than financial outcomes in shaping disclosure behaviour. These findings underscore that external pressures drive carbon disclosure rather than internal profitability. The study offers empirical insights for regulators, investors, and companies aiming to enhance sustainability and accountability in carbon-intensive sectors. However, this study is limited by its short observation period (2021–2024) and focus on selected high-polluting industries, which may restrict generalisability. Future research could extend the time horizon, examine other sectors, or include governance and ownership variables to provide a more comprehensive picture.